qanda-logo
search-icon
Símbolos
Problema
solution-image
@ $2x+7=3x+6$ Con x=2 $2\left(2\right)+3=3\left(x\right)+6$ $4+7=6+6$ $11=+12$ 2 $3x+5=6x-1$ Con X=4 $3\left(4\right)+5=6\left(4\right)-1$ $12+5=24-1$ $17=+23$ 3 $9x+8=7x+5$ - con $x=6$ $9\left(6\right)+8=7\left(6\right)+5$ $54+8=42+5$ $62=+47$ A $2x+9=3x-3$ con $x=9$ $2\left(9\right)+9=3\left(9\right)-3$ $18+9=27-3$ $27=+24$
Bachillerato
Aritmética y álgebra
Búsquedas: 108
Solución
answer-user-profile-image
Profesor de Qanda - FlavioMora
answer-reply-image